A expressão da ideologia no artigo do mestre - Wojtowicz, Licéria (2004)
Textual genres, while communicative events, have been the focus of interest of researchers who aim at explaining the process involved in their manifestation. The Master s Article of the Sheicho-No-Ie Fonte de Luz issue was chosen as corpus. Texts that were published from October 1996 to March 2004, signed by Masaharu Taniguchi were selected to verify the features which comprise these texts as textual genres. Teun van Dijk was chosen as the basis for the analysis of certain structures which can portray ideology. The analysis was also supported by Meurer (1997a, 1997b, 1998, 2002) on a distinction between textual genre and rethorical mode, and on the concepts of Halliday & Hasan (1998) about the relation of text and context. The religious issue was based on the studies of Orlandi (1987), and the concepts of self-help were supported by Chagas (1999, 2002). It was observed the occurrence of basic textual structures of situation-problem-evaluation-solution and hypotheticality. In relation to speech acts there was a prevalence of questions, statements and threatening. In the microstructural analysis it was observed that the modalizers, the pronoun we, and the connector if, among other discoursive structures, portray ideological meanings. It was also observed the narrative, description, exortation and exposition as rethorical mode. This study intends to contribute to researches in the area of language, through the description of a religious-oriented genre, and to bring some light into the discussions of ideologycal issues, which are implicit in the master s discourse, as well as, to show how social and religious representations are expressed in genres, which are part of the society, and which are perpetuated through language.